IMPORTANCE OF CLASSIFICATION OF HISTORICAL TERMS AND CONCEPTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the importance of determining the role of historical concepts in the study of history, to consider the classification of historical concepts, to highlight the features of the formation of concepts in the process of teaching history.